Relationship of diabetes to atherosclerotic plaque characteristics of coronary artery lesions by differing angiographic stenosis severity. (14th October 2021) - Jonas, R; Crabtree, T; Jennings, R; Choi, A; Earls, J; Min, J; ,
Abstract: Background: There is a strong relationship between atherosclerotic plaque characteristics (APCs) and major adverse cardiovascular events. However, whether APCs are different in obstructive vs. non-obstructive lesions, and whether diabetic status modifies this relationship is unknown. Purpose: This study examines the relationship between APCs and angiographic stenosis severity in diabetic vs. non-diabetic patients. Methods: We evaluated 303 subjects referred for invasive coronary angiography with coronary computed tomographic angiography and classified lesions as obstructive (>50%) or non-obstructive using blinded quantitative coronary angiography. APCs, including plaque volume (PV), low density non-calcified plaque (LD-NCP), non-calcified plaque (NCP), calcified plaque (CP), lesion length, positive remodeling (PR), and high-risk plaque (HRP) were quantified and normalized for vessel volume. The relationship between APCs and angiographic stenosis severity was compared in diabetics vs. non-diabetics. Results: Among 362 coronary lesions observed, 48.3% were obstructive, 51.7% were non-obstructive. In diabetics, NCP was significantly higher in obstructive vs. non-obstructive lesions (p=0.0033); however, in non-diabetics, no difference was observed (p=0.0525). In non-diabetics, PR was significantly higher in non-obstructive vs. obstructive lesions (p=0.0424); however, among diabetics, no difference was observed (p=0.7509). Comparing ACPs in obstructive lesions between diabetics and non-diabetics, diabetics had less NCP and HRP, more CP, PR and LD-NCP with comparable PV and lesion lengths. Comparing APCs in non-obstructive lesions, diabetics had greater PV, CP and PR with less LD-NCP, NCP, HRP, and shorter lesion lengths. Conclusion: In diabetics, NCP is significantly higher in obstructive vs. non-obstructive lesions. Thus, measuring NCP may help identify high-grade stenotic lesions in this population. Funding Acknowledgement: Type of funding sources: None.